Prevalence and risk factors for blood filariasis among HIV-infected adults in Gabon, Central Africa: a pilot study - Pongui Ngondza, B; Koumba Lengongo, J V; Mickala, P; M'bondoukwé, N P; Ndong Ngomo, J M; Moutombi Ditombi, B C; Mawili-Mboumba, D P; Bouyou-Akotet, M K (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2022)
The level of blood filariasis parasitaemia as well as the frequency of and the relationship between cotrimoxazole prophylaxis (CTX-P), antiretroviral therapy (ART) intake and CD4 cell count among people living with human immunodeficiency virus (PLHIV) in rural areas of Gabon were being studied. Sociodemographic data and recent biological tests of PLHIV and HIV-negative participants were collected. Loa loa and Mansonella perstans microfilaria were detected by direct microscopy examination and leucoconcentration. Overall, 209 HIV-positive and 148 HIV-negative subjects were enrolled. The overall prevalence of microfilaria was comparable between PLHIV (19.9% [n=41/206]) and HIV-negative participants (14.8% [n=22/148]) (p=0.2). The L. loa infection rate was comparable between HIV-positive (9.2%) and HIV-negative participants (6.8%) (p=0.2), while the M. perstans infection rate was 14-fold higher among PLHIV (p<0.01). L. loa parasitaemia was 6-fold lower in PLHIV receiving CTX-P (median 150 mf/mL [interquartile range IQR 125-350]) than in patients without (900 [550-2225]) (p<0.01). Among subjects with a CD4 cell count <200 cells/μL, the prevalence of M. perstans was 7-fold higher than that of L. loa (20.6% vs 2.9%). This study suggests a similar exposure to L. loa infection of PLHIV and HIV-negative patients while M. perstans is more frequently found in HIV-positive individuals, notably those with a CD4 count <200 cells/μL.